Jom Sains 2023 / Associate Prof. Dr. Mizaton Hazizul Hasan and Dr. Gurmeet Kaur Surindar Singh - Hasan, Mizaton Hazizul; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
Jom Sains Farmasi 2023, held on August 29th, was an engaging scientific programme designed for children between the ages of 6 and 12. This activity was organised by the Faculty of Pharmacy at UiTM Puncak Alam. The programme had been conducted on a yearly basis starting in 2017 until it was interrupted by the implementation of the movement control order (MCO) due to the COVID-19 pandemic in 2020. We are glad to resume this event once again this year to stimulate the curiosity and engagement of young students in the domains of science, technology, engineering, and mathematics (STEM) education while simultaneously offering them an initial exposure to the profession of pharmacy. The primary objective of the project was to foster a passion for science, especially in the field of pharmacy, among the children while also imparting a diverse range of scientific principles and skills. The curriculum is additionally in accordance with the World Health Organisation's Sustainable Development Goal 4, which aims to ensure inclusive and fair access to high-quality education and foster opportunities for lifelong learning for all individuals.